2023
DOI: 10.3390/children10020181
|View full text |Cite
|
Sign up to set email alerts
|

Pediatric Glaucoma—From Screening, Early Detection to Management

Abstract: Pediatric glaucoma (PG) covers a rare and heterogeneous group of diseases with variable causes and presentations. Delayed diagnosis of PG could lead to blindness, bringing emotional and psychological burdens to patients’ caregivers. Recent genetic studies identified novel causative genes, which may provide new insight into the etiology of PG. More effective screening strategies could be beneficial for timely diagnosis and treatment. New findings on clinical characteristics and the latest examination instrument… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
0
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(2 citation statements)
references
References 192 publications
0
0
0
Order By: Relevance
“…Six published reports have consistently identified PCG as the prevalent common subtype, with studies from Egypt (55.07% from 207 samples [7]; 68.25% from 652 samples [8]), the USA (19.2% from 205 samples [9]), Brazil (43.95% from 496 samples [10]), India (35.27% from 275 samples [11]), and Australia/New Zealand (57.59% from 290 samples [4]). In contrast, two studies from Thailand and Boston have identified PCG (20.8% in Thailand; 29% in Boston) as the second most common subtype [12]. These findings underscore the variability in prevalence among different geographic populations and suggest potential genetic influences.…”
Section: Introductionmentioning
confidence: 76%
“…Six published reports have consistently identified PCG as the prevalent common subtype, with studies from Egypt (55.07% from 207 samples [7]; 68.25% from 652 samples [8]), the USA (19.2% from 205 samples [9]), Brazil (43.95% from 496 samples [10]), India (35.27% from 275 samples [11]), and Australia/New Zealand (57.59% from 290 samples [4]). In contrast, two studies from Thailand and Boston have identified PCG (20.8% in Thailand; 29% in Boston) as the second most common subtype [12]. These findings underscore the variability in prevalence among different geographic populations and suggest potential genetic influences.…”
Section: Introductionmentioning
confidence: 76%
“…Interventional studies with a prospective cohort design are essential to increase adherence and reduce bias. For prompt diagnosis and treatment, more effective screening techniques may be useful [ 27 ]. Devastating visual results might result from delays in presentation, diagnosis, and management.…”
Section: Discussionmentioning
confidence: 99%